Impact of a Pharmacist-Driven Respiratory Viral Panel Stewardship Program on Antibiotic Exposure Within a Multicenter Community Health System. (4th October 2017) - Cubillos, Ashley; Estrada, Sandy; Bachmeier, Harrison; Turner, Edgar
Abstract: Background: Strategies to ensure optimal use of multiplex polymerase chain reaction (mPCR) testing results for antimicrobial stewardship in acute respiratory infections remain to be elucidated. This study sought to assess the impact of pharmacist intervention (by means of prospective feedback to prescribers) on overall antibiotic exposure in patients with viral-positive mPCR Respiratory Viral Panel (RVP) laboratory test results. Methods: This retrospective cohort study included patients ≥18 years of age admitted to an acute care hospital with a viral-positive nasopharyngeal FilmArray Respiratory Panel test result receiving antibiotics for a suspected respiratory tract infection. Immunocompromised patients, patients with RVP samples from bronchiolar lavage, patients in the intensive care unit when samples were obtained, and patients receiving antibiotics for non-respiratory infections were excluded. Antibiotic exposure days, antibiotic discontinuation at 72 hours, and culture-positive bacterial superinfection were compared in two cohorts of patients, before and after the rollout of an educational pharmacist RVP stewardship initiative. Results: Median antibiotic exposure days did not differ between the pre- and post-intervention groups (6 days vs. 7 days, P = 0.20). Antibiotic discontinuation at 72 hours was significantly lower in the post-intervention group (38% vs. 25%, P = 0.02). More patients in the post-intervention group had positive bacterial respiratory cultures (2.7% vs. 10%, P = 0.007) and chest radiographs suggestive of pneumonia (34.7% vs. 46%, P = 0.05). Patients with peak serum procalcitonin levels <0.25 ng/mL were more likely to have antibiotics discontinued at 72 hours than those with peak levels ≥0.25 ng/mL (36% vs. 0%, P = 0.02). Conclusion: An antimicrobial stewardship initiative by pharmacists among patients with viral-positive RVP results did not appear to impact antibiotic exposure days. Serum procalcitonin levels appeared to influence antibiotic discontinuation decisions. Alternative strategies for maximizing the antimicrobial stewardship impact of RVP testing should be explored. Disclosures: All authors: No reported disclosures.